Potential of biosurfactants as antiadhesive biological coating - Alara, Oluwaseun Ruth (Elsevier, 2023)
Microbial diseases associated with microbial adhesion to biomaterial surfaces have been reported in almost every medical device with medical and economic consequences. Antimicrobial resistance is the major cause of biofilm infections and has led to many clinical challenges, such as chronic inflammatory diseases and swiftly acquired drug resistance. The demand for materials protected with molecules that inhibit the adhesion of microbes that produce biofilms has increased. Biosurfactants could be used on surfaces of economic attraction as coating agents that prevent microbial formation. Given the challenge in restoring implant Osseo integration after peri-implantitis, some years ago, biomaterials and methods were established and examined to eradicate bacterial colonization and promote close contact and growth of peri-implant body tissues with the coating surface. These techniques can act via several mechanisms, such as the antiadhesive treatment’s ability to modify implant surface energy, microbial adhesion, and surface coating with biosurfactants with biocidal activity. However, because of the antimicrobial resistance of microbial biofilms to conventional antibiotic treatments, several studies on infection prevention have been stimulated by creating anti-adhesives and anti-infective devices. The potency of the anti-adhesive biological coating potential of biosurfactants to mitigate adhesion by modifying the surface activities has decreased and depends highly on the bacterial species. Hence, this chapter discusses the process and mechanism of microbial adhesion and biofilm, different types of biosurfactants with anti-adhesive properties, the production of anti-adhesive and anti-infective biomaterial, and some results of the inventions related to the anti-adhesive biological coating effect of biosurfactants.